2022
DOI: 10.1681/asn.2021070935
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin Prevents Kidney Glycogen Accumulation and Improves Renal Proximal Tubule Cell Functions in a Mouse Model of Glycogen Storage Disease Type 1b

Abstract: Background: Mutations in SLC37A4, which encodes the intracellular glucose transporter G6PT, cause the rare glycogen storage disease type 1b (GSD1b). A long-term consequence of GSD1b is kidney failure, which requires kidney replacement therapy. The main protein markers of proximal tubule function, including NaPi2A, NHE3, SGLT2, GLUT2, and AQP1, are downregulated as part of the disease phenotype. Methods: We utilized an inducible mouse model of GSD1b, TM-G6PT-/-, to show that glycogen accumulation plays a crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Dapagliflozin minimized further glucose influx and not only prevented cortical glycogen accumulation but also increased the membrane expression of SGLT2 as an indication of improved PT cell function. We have demonstrated a similar process in the glycogen storage disease Ib ( 12 , 13 ).…”
Section: Discussionsupporting
confidence: 60%
“…Dapagliflozin minimized further glucose influx and not only prevented cortical glycogen accumulation but also increased the membrane expression of SGLT2 as an indication of improved PT cell function. We have demonstrated a similar process in the glycogen storage disease Ib ( 12 , 13 ).…”
Section: Discussionsupporting
confidence: 60%
“…As such, variable stages of kidney disease, from proximal and distal tubulopathies to irreversible glomerular injury, may affect the outcome of these patients [115]. In a mouse model of GSD1b that accumulated glycogen in the kidney, Trepiccione and collaborators [116] showed that the main protein markers of proximal tubule function were all down-regulated. These markers included the major sodium and phosphate transporters along the proximal tubule (NHE 3 and NaPi2A), the two main renal glucose transporters located on the apical and the basolateral membranes of the proximal tubular cells (SGLT2 and GLUT2) and AQP1, the principal aquaporin water-transporting protein in the plasma membranes of the proximal tubular cells.…”
Section: Could Sglt2 Inhibitors Help Gsd1b Patients Beyond Treating T...mentioning
confidence: 99%
“…Indeed, empagliflozin reduces NHE3 transport activity in rats, showing a tight relation between SGLT2 and NHE3 transporters [ 46 ]. This has been recently highlighted in a mice model mimicking the Fanconi syndrome secondary to glycogen storage disease 1b [ 47 ].…”
Section: The Roles Of Nhe3 In the Control Of Blood Pressurementioning
confidence: 99%